PENGEMBANGAN SISTEM INFORMASI RAWAT JALAN (STUDI KASUS : RSUD KRATON PEKALONGAN JAWA TENGAH) - Atin Triwahyuni (Jurnal Informatika, 2013)
RSUD Kraton Pekalongan Central Java is one of the Public Service Board which is engaged in health care, especially for society in pekalongan and the surrounding counties. One of the existing service is outpatient treatment services which operationally has many obstacles due to the large volume of patient visits without any supported by tools such as computer-based information sistems. This study tries to provide an alternative model of outpatient administration by using the information sistem of architecture client/server applications which can connect several parts involved in outpatient operations. by this administration sistem of patient registration, action and the use of medical devices and prescription services can be assisted by using the sistem, then the entire bill of patient can be easily displayed through the cashier menu as billing patients attending for treatment in outpatient installation.Keywords: Outpatient, Client/Server, RSUD Kraton